2019
DOI: 10.1371/journal.pntd.0007562
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing patients with laboratory-confirmed chikungunya from dengue and other acute febrile illnesses, Puerto Rico, 2012–2015

Abstract: Chikungunya, a mosquito-borne viral, acute febrile illness (AFI) is associated with polyarthralgia and polyarthritis. Differentiation from other AFI is difficult due to the non-specific presentation and limited availability of diagnostics. This 3-year study identified independent clinical predictors by day post-illness onset (DPO) at presentation and age-group that distinguish chikungunya cases from two groups: other AFI and dengue. Specimens collected from participants with fever ≤7 days were tested for chiku… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
19
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 55 publications
(69 reference statements)
4
19
1
1
Order By: Relevance
“…Without diagnostics, chikungunya infection is difficult to distinguish from other acute febrile illnesses caused by common arboviruses like dengue viruses or Zika virus. Previous reports have described that chikungunya cases have higher viremia than dengue and Zika (40). In contrast, others have reported that dengue cases have lower leucopenia and thrombocytopenia compared to cases of chikungunya or Zika (71).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Without diagnostics, chikungunya infection is difficult to distinguish from other acute febrile illnesses caused by common arboviruses like dengue viruses or Zika virus. Previous reports have described that chikungunya cases have higher viremia than dengue and Zika (40). In contrast, others have reported that dengue cases have lower leucopenia and thrombocytopenia compared to cases of chikungunya or Zika (71).…”
Section: Discussionmentioning
confidence: 86%
“…Chikungunya virus causes similar clinical manifestations during the acute phase that could mimic other arboviruses, and there are no widely available point-of-care rapid diagnostics (43,64,65). For these reasons, clinicians working in endemic regions and those treating returning travelers are challenged with diagnosing chikungunya infection (40,(66)(67)(68).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A subset of individuals exhibit atypical manifestations, and some develop a chronic course of illness [ 36 , 37 , 38 ]. Based on clinical and laboratory profiles, it is difficult for clinicians to distinguish chikungunya infection from other circulating pathogens such as dengue and Zika viruses [ 39 , 40 ]. To overcome this obstacle, researchers at the Mahidol-Osaka Center for Infectious Diseases at Mahidol University in Thailand, in collaboration with the Department of Viral Infections at Osaka University in Japan, have developed a novel prototype rapid point-of-care immunochromatography test kit that identifies suspected chikungunya cases based on detection of the E1 antigen [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“… 9 Of note, others haemorrhagic manifestations, such as skin and mucosal bleeding, were considered positive predictor of Chikungunya infection among patients with suspected arbovirus infection. 10 …”
mentioning
confidence: 99%